Multi-Attribute Utility Theory for Selecting an Appropriate Procurement Method in the Construction Projects - Sawalhi , Nabil I. El; Agha, Osama El (Penerbit Universiti Sains Malaysia, 2017)
The selection of an appropriate procurement method is becoming an increasingly important issue due to complex decision making that clients are facing early in the lifecycle of construction projects. The aim of this paper is to improve the procurement system in the construction industry by developing a model using the multi-attribute utility theory (MAUT) as a decision support system for the selection of an appropriate procurement method for construction projects in the Gaza Strip. Factors that influence the selection of an appropriate method for construction projects in the Gaza Strip are identified and the results indicate that the most significant six factors influencing the selection of procurement methods in the Gaza Strip construction projects are price competition, degree of project complexity, time constraints of the project, project size, client financial capability and client experience in procurement methods. The study concludes that there is no variety of procurement methods used in the Gaza Strip construction industry, as a traditional procurement method is preferred. This is because most professionals in the Gaza Strip are not familiar or experienced with alternative procurement methods. A model was developed using the MAUT to select the most appropriate procurement method. The MAUT as a decision support system was successful in identifying the appropriate procurement method.